Morphological and biochemical characterization of Rhizobium isolates obtained from fenugreek (Trigonella foenum) - ALKA PANWAR; SHARDA CHOUDHARY; MANOJ SHARMA; Y.K. SHRAMA; R.S. MEENA; S.K. MALHOTRA; R.S. MEHTA; O.P. AISHWATH (Seed Research, 2026)
Fenugreek (Trigonella foenum graecum L.), a seed spice, is known for its dietary protein source, medicinal properties and symbiotic nitrogen fixation by Rhizobium bacteria present in its root nodules. The study was carried out to characterize Rhizobium strains isolated from root nodules of fenugreek. The isolates were identified and characterized on the basis of colony morphology and biochemical traits viz. gram staining, catalase, and oxidase tests, and utilization pattern such as citrate utilization activity, nitrate reduction and methyl red test. The Rhizobium isolates were rod-shaped, gram negative, acid and mucous producing. They were found to be sensitive to temperature and pH, at 27°±1°C and 6.8±0.2, respectively. It utilizes starch as sole carbon source.